PerPot - a meta-model and software tool for analysis and optimisation of load-performance-interaction - Perl, J. (International Journal of Performance Analysis in Sport, 2004)
The Performance Potential meta-model PerPot simulates the interaction between load and performance in adaptive physiological processes like training in sport by means of antagonistic dynamics.